2020
DOI: 10.1101/2020.10.20.20216283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in knowledge of HIV status and efficiency of HIV testing services in Sub-Saharan Africa (2000-2020): a modelling study of survey and HIV testing program data

Abstract: Background: Knowledge of HIV status (KOS) among people living with HIV (PLHIV) is essential for an effective national HIV response. This study estimates progress and gaps in reaching the UNAIDS 2020 target of 90% KOS, and the efficiency of HIV testing services (HTS) in sub-Saharan Africa (SSA), where two thirds of all PLHIV live. Methods: We used data from 183 population-based surveys (N=2.7 million participants) and national HTS programs (N=315 country-years) from 40 countries as inputs into a mathematical mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The corresponding rates were only 68-58-45 in West and Central Africa ( 2 ). The last published data confirmed that the rates of knowledge of HIV status by PLHIV are much lower in the countries of West and Central Africa, than those from Eastern and Southern Africa ( 3 ).…”
Section: Introductionmentioning
confidence: 84%
“…The corresponding rates were only 68-58-45 in West and Central Africa ( 2 ). The last published data confirmed that the rates of knowledge of HIV status by PLHIV are much lower in the countries of West and Central Africa, than those from Eastern and Southern Africa ( 3 ).…”
Section: Introductionmentioning
confidence: 84%
“…The lack of such identifiers has limited many previous attempts to understand PLHIV movements within health systems and obstructed attempts to provide high-quality person-centered care. In an attempt to answer one such question, a recent analysis of household survey and HIV testing program data across sub-Saharan Africa estimated that "58% of positive tests will have been done on previously diagnosed PLHIV in sub-Saharan Africa in 2020" [36]. If this trend is further validated, efforts to retain and reengage people who have interrupted treatment will become a higher yield activity than population-wide testing to make new HIV diagnoses.…”
Section: Populating and Using The Cyclical Cascadementioning
confidence: 99%
“…UNAIDS has set targets for 95% of people living with HIV to know their status, 95% of known HIV-positive individuals to be on antiretroviral therapy (ART), and 95% of those on ART to have their viral load suppressed by 2030 ( 5 ). Despite significant progress on the proportion of individuals who know their HIV status (increase from 4% in 2000 to 67% in 2020), Western Africa remains far below the first 90 UNAIDS target, with disparities observed between Côte d'Ivoire (76%), Senegal (78%), and Mali (48%) in 2020 ( 6 ).…”
Section: Introductionmentioning
confidence: 99%